Juridical Review of Land Acquisition for Public Interest Based on Law Number 2 of 2012 concerning Land Acquisition for Public Interest - Muchtar, Andhyka; Yani, Akhmad; Nasir, Muh (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Regulations on Land Acquisition for development in the public interest are regulated in Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest and its Implementing Regulations are regulated by Presidential Regulations and Regulations of the Head of the National Land Agency of the Republic of Indonesia. Land acquisition for development in the public interest is carried out through several stages, namely planning, preparation, implementation and delivery of results. Implementation of land acquisition also often intersects with fundamental legal issues such as human rights, the principle of justice, the principle of balance between the interests of the state and the interests of society both in terms of individual or group. This article was written using the method normative legal research In this type of legal research, law is often conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or norm.